2020
DOI: 10.1111/ejh.13375
|View full text |Cite|
|
Sign up to set email alerts
|

Blinatumomab vs historic standard‐of‐care treatment for minimal residual disease in adults with B‐cell precursor acute lymphoblastic leukaemia

Abstract: Objectives Survival outcomes from a single‐arm phase 2 blinatumomab study in patients with minimal residual disease (MRD)‐positive B‐cell precursor (BCP)‐acute lymphoblastic leukaemia (ALL) were compared with those receiving standard of care (SOC) in a historic data set. Methods The primary analysis comprised adult Philadelphia chromosome (Ph)‐negative patients in first complete haematologic remission (MRD ≥ 10−3). Relapse‐free survival (RFS) and overall survival (OS) were compared between blinatumomab‐ and SO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 55 publications
(213 reference statements)
0
19
0
Order By: Relevance
“…The method relies on a readily available source of stem cells and avoids GVHD and labor-intensive steps of other models. Our model of early treatment with blinatumomab after engraftment mimics several completed and ongoing clinical trials in which blinatumomab has been used against residual post chemotherapy MRD (7,10,20). One question that remains unanswered is if blinatumomab could be used concurrently or consecutively with conventional chemotherapy, and how the lymphotoxic effects of chemotherapy impact efficacy of blinatumomab (21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The method relies on a readily available source of stem cells and avoids GVHD and labor-intensive steps of other models. Our model of early treatment with blinatumomab after engraftment mimics several completed and ongoing clinical trials in which blinatumomab has been used against residual post chemotherapy MRD (7,10,20). One question that remains unanswered is if blinatumomab could be used concurrently or consecutively with conventional chemotherapy, and how the lymphotoxic effects of chemotherapy impact efficacy of blinatumomab (21).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, new effective therapies for patients in relapse have further improved survival, including the CD19directed Bi-specific T cell Engager (BiTE), blinatumomab. As a treatment for therapy resistant disease, blinatumomab has been shown to lead to longer relapse free survival compared to historical data using standard chemotherapy approaches in adult patients (7). A group of 20 such patients who received blinatumomab achieved a long-term relapse free survival of 60-65% at 3 years, regardless of HSCT (8).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, early administration of blinatumomab is beneficial to B-ALL patients with MRD (NCT01207388) [ 48 ]. Compared with standard chemotherapy, blinatumomab was associated with a higher rate of CR and longer overall survival [ 49 ]. Moreover, administration of blinatumomab before allogeneic stem cell transplantation improved the rate of CR, which indicated that blinatumomab could be a bridge to allogeneic stem cell transplantation (NCT02013167) [ 50 ].…”
Section: Mechanisms Of Bite Actionmentioning
confidence: 99%
“…Historical control data also contributed to an expanded indication for this drug for the treatment of patients with minimal residual disease. 42 A more traditional example is the approval of intracerebroventricular cerliponase alfa for the treatment of infantile batten disease, where data from a dose escalation trial was compared against historical controls. 43 Despite mounting success of external controls to support drug approvals, there have also been some notable failures.…”
Section: External Controls Derived From Rwdmentioning
confidence: 99%